Anti-gout potential of selected Malaysian local fruits - Wan Aziz, W. N. A.; Abu Bakar, M. F.; Abu Bakar, F. I.; Dheyab, A. S.; Sabran, S. F.; Kormin, F. (2021)
This study aimed to investigate the in vitro xanthine oxidase (XO) inhibitory activity and phytochemical content of guava, water rose apple, Malay gooseberry, pineapple and ambarella. The xanthine oxidase inhibitory activity was measured spectrophotometrically at 295 nm. The phytochemical analysis tested were total phenolic, total flavonoid and total anthocyanin contents of each methanolic extract of the fruits. The highest amount of phenolic was found in ambarella (0.245 mg GAE/g) while guava had the highest amount of flavonoid (0.472 mg RE/g). Meanwhile, water rose apple had the highest anthocyanin content (5.001 mg c-3-gE/g). For the XO inhibitory activity, water rose apple displayed the lowest IC50 value (26.86 μg/mL), showing better anti-gout activity as compared to that of other fruit samples. Positive correlation between total phenolic content and XO inhibitory activity was also observed in this study. Further study on the isolation of bioactive compounds from the fruit samples that act as XO inhibitor is greatly needed in the future.